2022
DOI: 10.1177/00219983221137676
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization mechanism and mechanical properties of CF/PPS thermoplastic composites manufactured by laser-assisted automated fiber placement

Abstract: In situ consolidation of the thermoplastic composites can be realized through laser-assisted automated fiber placement technology, and the properties of the composites are significantly affected by the crystallinity. Understanding the complicated crystallization process is very important for controlling the performance of the composites manufactured by automated fiber placement. In this work, the crystallization mechanism of carbon fiber/polyphenylene sulfide composites during the automated fiber placement pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…When the tool temperature in the range of ithe crystallization window, the CF/PPS composite undergo the isothermal crystallization, which could increase crystallinity even further. The mechanical characteristics improved as the tool temperature increased due to improved matrix self-adhesion, whereas the fracture toughness declined due to lower matrix ductility [11,26]. kinetics, and weight loss of materials under controlled heating conditions.…”
Section: Degree Of Crystallinity (Doc)mentioning
confidence: 99%
See 1 more Smart Citation
“…When the tool temperature in the range of ithe crystallization window, the CF/PPS composite undergo the isothermal crystallization, which could increase crystallinity even further. The mechanical characteristics improved as the tool temperature increased due to improved matrix self-adhesion, whereas the fracture toughness declined due to lower matrix ductility [11,26]. kinetics, and weight loss of materials under controlled heating conditions.…”
Section: Degree Of Crystallinity (Doc)mentioning
confidence: 99%
“…This is because it influences the cooling rate of the formed components, resulting in different crystallization levels [8][9][10]. The investigation on CF/PPS composites manufactured using automated fibre placement by Zhao et al, [11] revealed that the tool temperature is the main factor influencing the crystallinity, and the properties of the CF/PPS composite are significantly affected by the crystallinity. Lona Batista et al, [8] also found that lower cooling rates during hot compression moulding processing resulted in higher DoC in the CF/PPS composites with the mechanical properties improved for the lower cooling rates.…”
Section: Introductionmentioning
confidence: 99%